IMPROVEMENT OF EXPANDED POLYSTRENE BARCODE SYSTEM AT PT KEMASAN CIPTATAMA SEMPURNA - Nailah, Ula Farhah; Handayani, Wiwik (International Journal of Economy, Education and Entrepreneurship (IJE3), 2024)
This research focuses on improving the barcode system at PT Kemasan Ciptatama Sempurna by integrating Internet of Things (IoT) technology and a MySQL database. The aim is to enhance inventory management and goods delivery efficiency. The research method used is Research and Development (R&D) to develop and test the proposed system. The highest sales products were identified as HMD001, HMD002, POT001, and POT002, while low sales items remained consistent, including item codes BOX001, BOX002, LBR001, and LBR002. The implementation of the barcode system integrated with a MySQL database resulted in reduced delivery lead times, optimized inventory management, real-time tracking of goods, decreased recording errors, and improved operational efficiency. Furthermore, the use of IoT in the barcode system provides additional benefits such as goods condition monitoring and automated inventory processes